Enneapterygius pallidoserialis, a Junior Synonym of Enneapterygius erythrosoma (Perciformes: Tripterygiidae) - Yuna Dewa; Hiroyuki Motomura (Species Diversity)
Enneapterygius pallidoserialis Fricke, 1997, previously considered a valid species, is regarded as a junior synonym of E. erythrosoma Shen, 1994. Re-examination of type specimens of both nominal species revealed that the meristic and morphometric characters of the holotype and seven paratypes of E. pallidoserialis examined closely matched those of the holotype, paratype, and non-type specimens of E. erythrosoma. Furthermore, the nuptial coloration of male specimens of E. pallidoserialis, including the holotype, was consistent with that of E. erythrosoma. This synonymization resulted in E. erythrosoma being newly recorded from Miyake-jima island (Izu Islands, Japan), and Putic and Siayan islands (Philippines) on the basis of specimens previously identified as E. pallidoserialis.